RESEARCH OF THE PROPERTIES OF PHOSPHATMOBILIZING BACTERIA PERSPECTIVE FOR INCREASING THE PRODUCTIVITY OF AGRICULTURAL GRAINS (Experimental biology, 2022)
Phosphorus is one of the main nutrients that ensure the formation of high and sustainable crop yields with a favorable quality of marketable products.One of the perspective directions for improving the phosphorus nutrition of agricultural crops is biological phosphate mobilization with the help of soil microorganisms, which promotes the transfer of sparingly soluble phosphorus compounds from soil and fertilizers into a form accessible to agricultural plants. Aboriginal soil phosphate-mobilizing bacteria were isolated from the rhizosphere soil of the northern region of the Republic of Kazakhstan. From 5 strains of phosphate-mobilizing bacteria 3 cultures with a high activity of soil phosphate mobilization were selected. Selected strains of phosphate-mobilizing bacteria are perspective as a basis for creating a complex biofertilizer for a wide range of agricultural crops.